Pengenalan Alat Navigasi, Keselamatan dan Kesehatan pada Kapal Penangkap Ikan Enterprise di Perairan Selat Makassar - Leopold A. Tomasila; Lolita C. Tuhumena; Silvester Sinau; Yvonne I. Pattinaja; Sara Umbekna (Universitas Pattimura, 2023)
On voyage fishing vessel should be equipped with proper navigation equipment. Cadets who will be working onboard of a fishing vessel should understanding and aware of navigational equipment, safety equipment and healthy equipment. Because ,it could cause accident and awareness on navigational equipment. One of the ways for cadets to understand about navigation equipment are Maps, Campasses, Global Positioning System, Radia and Automatic Identification System. Each of these navigation equipment are hhaving their own function and operating system. So, it is a mandatory for every cadets to understand and aware in operating sthes navigation and know about safety equipment and healthy equipment on Enterprise fishing vessel .